2019
DOI: 10.31298/sl.143.5-6.5
|View full text |Cite
|
Sign up to set email alerts
|

The effects of wood chips and slash usage on skid trail sheet erosion caused by log skidding using a farm tractor

Abstract: This study investigated the sheet erosion that occurs as a result of log skidding operations using a farm tractor on skid trails and the use of wood chips and slash in order to minimize the soil loss. A total of four blocks (sample fields) were formed in four designated skid trails in the study area and three runoff plots were established in each block. One of the runoff plots was left empty as a control (CNT). Wood chips (C) was placed in the second plot and logging residue slash (S) in the third. A total of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 4 publications
0
1
0
2
Order By: Relevance
“…Many researchers demonstrated that logging residues or slash can be used to reduce the sheet erosion that occurs on skid trails after log extraction (Wagenbrenner et al 2016;Turk, Yildiz 2019). Particle detachment is caused by both raindrop impact (splash erosion) and superficially flowing water.…”
Section: Discussionmentioning
confidence: 99%
“…Many researchers demonstrated that logging residues or slash can be used to reduce the sheet erosion that occurs on skid trails after log extraction (Wagenbrenner et al 2016;Turk, Yildiz 2019). Particle detachment is caused by both raindrop impact (splash erosion) and superficially flowing water.…”
Section: Discussionmentioning
confidence: 99%
“…Kretanje skidera uzrokuje nastanak kolotraga i pomjeranje tla zbog slabe strukture u gornjim slojevima traktorskih puteva/vlaka (Eliasson, 2005). Kada se proces privlačenja odvija preko istog mjesta, nosi se mineralno tlo i formiraju se kanali osjetljivi na eroziju koji mogu uzrokovati ozbiljne probleme tokom obilnih padavina (Turk & Yildiz, 2019). Vodna erozija uzrokuje ozbiljna oštećenja, posebno na kolotrazima traktorskih puteva/vlaka (Naghdi et al, 2012).…”
Section: Dynamics Of Development Of Erosion Processes On Skid Roads -...unclassified
“…O značaju proučavanja erozionih procesa na traktorskim putevima/vlakama jasno ukazuju brojne studije i naučno-istraživački radovi koji su provedeni od strane više istraživača (Meghatan and Kidd, 1972;Jeličić 1983Jeličić , 1990Rebula 1991;Krpan i drugi, 1993;Tomašić, 1994;Pičman i Pentek 2001, Sasaki 2004, Eliasson 2005Bajrić 2012Bajrić , 2015Bajrić , 2021Grace 2006;Grushecky et et al, 2007;Elliot et al, 2009;Naghdi et al, 2012;Bagheri et al, 2012;Turk & Yildiz, 2019;Solgi et al, 2019;DeArmond et al, 2021;Jourgholami et al, 2021 i drugi istraživači).…”
Section: Dynamics Of Development Of Erosion Processes On Skid Roads -...unclassified